Sideways Stories from Wayside School - Louis Sachar (London Bloomsbury Publishing Plc, 2010)
There has been a terrible mistake. Wayside School was supposed to have been built with thirty classrooms all next to each other in a row. Instead it was built with the thirty classrooms all on top of each other - thirty storeys high! That may be why all kinds of strange stuff happens at Wayside School. Especially on the thirtieth floor. It is a school full of unusual characters too. Mrs Gorf, the meanest teacher in the world. Terrible Todd who always gets sent home early. John who can only read upside down. It is a crazy mixed-up school, brilliantly brought to life by the irresistible Louis Sachar.